Selected Subjects of Balochi Proverbs - Shahani, Shafique Ahmed; Rashid, Abdul Qudoos Hassan (sourcecoder, 2024)
Khalifo Nabi Baksh ’Qasim’ is a classical Poet of Sindh (1776 AD-1663) in talpur Perod (1843 AD-1783).He belong from noble class but he chose the path of mysticism and florish as a Poet of sindhi and srieki languages. He wrote a apic of the war of khar-ri, which is august classical poetry. No doubt he inspired great Sindhi poet shah abdul latif bhittai. His poetry is a beautiful continuety of Sindhi classical poetry. He depicts so many kinds of images in the Sindhi poetry, which is good addition of classical poetry. This research paper is enlighting the partly study of images of khalfo nabi baksh ’Qasim’ poetry.